Cutaneous Reactions to Continuous Glucose Monitoring and Continuous Subcutaneous Insulin Infusion Devices in Type 1 Diabetes Mellitus. (July 2021) - Rigo, Rachel S.; Levin, Laura E.; Belsito, Donald V.; Garzon, Maria C.; Gandica, Rachelle; Williams, Kristen M.
Background: Continuous glucose monitoring (CGM) and continuous subcutaneous insulin infusion (CSII) are the standard of care for type 1 diabetes in children. There is little reported on device-related skin complications and treatment options. This study documents cutaneous reactions to CGM and CSII devices in children and young adults with type 1 diabetes. Methods: One hundred and twenty-one subjects (3-25 years) with type 1 diabetes and CGM and/or CSII use were recruited over a three-month period from the Naomi Berrie Diabetes Center at Columbia University Irving Medical Center. A five-question survey was completed for each subject detailing demographic data, diabetes management, and device-related skin complications. Results: Sixty percent of subjects reported skin complications related to CGM and/or CSII use. Terms most frequently used to describe cutaneous reactions were "red, " "itchy, " "painful, " and "rash." Subjects who used both CGM and CSII were more likely to report skin problems than those who used only CSII (odds ratio 2.9, [95% confidence interval: 1.2-6.7]; P = .015). There were no associations between skin complications and sex or race/ethnicity. Twenty-two percent of subjects with adverse skin event(s) discontinued use of a device due to their skin problem. Seven percent were evaluated by a dermatologist. Eighty-one percent used a range of products to treat their symptoms, with variable perceived clinical outcomes. Conclusions: Skin complications related to CSII or CGM devices are commonly reported in pediatric patients with type 1 diabetes and may lead to interruption or discontinuation of device use. Future studies are needed to elucidate the causes of these reactions and determine the best methods for prevention.